Introduction of standardised packaging and availability of illicit cigarettes: a difference-in-difference analysis of European Union survey data 2015–2018 - Laverty, Anthony A (Thorax, 2021)
Standardised packaging of tobacco products is intended to reduce the appeal of smoking, but the tobacco industry claims this increases illicit trade. We examined the percentage of people reporting being offered illicit cigarettes before and after full implementation of standardised packaging in the UK, Ireland and France and compared this to other European Union countries. Reported ever illicit cigarette exposure fell from 19.8% to 18.1% between 2015 and 2018 in the three countries fully implementing the policy, and from 19.6% to 17.0% in control countries (p for difference=0.320). Standardised packaging does not appear to increase the availability of illicit cigarettes.